Mediating Structures in Sámi Language Revitalisation - Sarivaara, Erika; Keskitalo, Pigga (Social Inclusion, 2016)
The revitalisation of the Sámi languages and support for language domains are central educational measures in the post-assimilation situation in Northern Europe. Taking critical indigenous education as the starting point, this meta-theoretical article discusses language revitalisation through mediating structures. Mediating structures provide the tools necessary to use language revitalisation as a means to counter the legacy of assimilation that has seriously affected the Sámi languages and caused language change. The article brings together recent research on the revitalisation of the Sámi languages. These studies are oriented towards the present situation of the Sámi languages and efforts to revive the languages. Relying on previous studies as well as new research, the article presents a communal model of language recovery, which facilitates an increase in the number of language speakers and also supports language domains. Such a mediating language revitalisation model builds social harmony in a postcolonial situation. The article emphasises the key tasks involved in the recovery of endangered languages.